2020
DOI: 10.1097/md.0000000000019657
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based FTIR-ATR spectroscopy coupled with extreme gradient boosting for the diagnosis of type 2 diabetes

Abstract: Timely diagnosis of type 2 diabetes and early intervention and treatment of it are important for controlling metabolic disorders, delaying and reducing complications, reducing mortality, and improving quality of life. Type 2 diabetes was diagnosed by Fourier transform mid-infrared (FTIR) attenuated total reflection (ATR) spectroscopy in combination with extreme gradient boosting (XGBoost). Whole blood FTIR-ATR spectra of 51 clinically diagnosed type 2 diabetes and 55 healthy volunteers were collected. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Random forest (RF) is an ensemble algorithm based on multiple random trees as the base classifiers, and has demonstrated its efficiency for biomedical prediction problems [ 36 ]. XGBoost is a popular fast classifier to handle various biomedical data types, including the spectroscopy spectrum and bioelectrical data [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Random forest (RF) is an ensemble algorithm based on multiple random trees as the base classifiers, and has demonstrated its efficiency for biomedical prediction problems [ 36 ]. XGBoost is a popular fast classifier to handle various biomedical data types, including the spectroscopy spectrum and bioelectrical data [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our study we used IR spectroscopy, which has been adopted for the characterization of biological materials, like tissue sections, cytological and histological specimens or biofluids, particularly serum samples. Using this technique to analyze serum samples, Ghimire et al [ 68 ] identified mouse lymphoma and melanoma, while Gajjaee et al [ 28 ] showed spectral changes in blood samples from patients with ovarian cancer. IR spectroscopy was useful for the estimation of serum cortisol levels in athletes [ 69 ], whereas Lechowicz et al [ 29 ] used FT-IR spectroscopy to enable the differentiation between sera from patients with rheumatoid arthritis (RA) and non-RA sera.…”
Section: Discussionmentioning
confidence: 99%
“…The superior XGBoost method indicates a real potential for the accurate detection of prediabetes within individuals. 83 Guang et al 84 also utilized ATR FT-IR spectroscopy in combination with XGBoost to analyze whole blood samples, here with the intention of diagnosing T2DM. Whole blood was collected from 51 T2DM individuals and 55 healthy individuals.…”
Section: General Application Of Chemometric Methods For Indicating Diabetes Within Various Biological Samplesmentioning
confidence: 99%